1987
DOI: 10.1002/aic.690331215
|View full text |Cite
|
Sign up to set email alerts
|

Use of a finite‐element method to interpret rheological effects in blade coating

Abstract: Data and finite-element simulations are presented for the blade coating of a series of Newtonian and non-Newtonian fluids. Numerical simulations for purely viscous fluids show good agreement with coating thickness data for Newtonian and relatively inelastic non-Newtonian liquids, including geometries for which lubrication theory is inaccurate. These simulations account for the shape of the free surface, with surface tension included, and incorporate realistic inflow and outflow boundary conditions. By comparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 10 publications
1
18
0
1
Order By: Relevance
“…The reduction in flowrate as a function of surface roughness parameters was calculated for triangular cavities/asperities with 30, 60, and 90°D angles. The reduction R is defined as follows: (3) where Qmugh is the flowrate calculated for a given rough surface and Qh••• is the flowrate obtained for planar Couette flow with h. vg taken as the channel height. Hence (see Fig.…”
Section: Pure Couette Flowmentioning
confidence: 99%
“…The reduction in flowrate as a function of surface roughness parameters was calculated for triangular cavities/asperities with 30, 60, and 90°D angles. The reduction R is defined as follows: (3) where Qmugh is the flowrate calculated for a given rough surface and Qh••• is the flowrate obtained for planar Couette flow with h. vg taken as the channel height. Hence (see Fig.…”
Section: Pure Couette Flowmentioning
confidence: 99%
“…It has been already underlined that, although the blade coating is a steady state process, the fluid particles experience a rapid Lagrangian acceleration under the blade [12]. Sullivan In their experiments, these two characteristic times were of the same order of magnitude.…”
Section: Fabric Parametersmentioning
confidence: 95%
“…In order to determine the influence of the elasticity independently of the viscosity, it is necessary to prepare fluids with variable elasticity while keeping the same viscosity. In a similar manner to the experiments of Sullivan et al [11,12] small amounts of PAA (0.025-0.2%) were added to HV polymer solutions at 1.5%. The results showed that when γ .…”
Section: Fabric Parametersmentioning
confidence: 99%
“…More sophisticated existing studies dedicated to blade-coating tend to confirm these conclusions and go farther: for simple liquids h remains inferior to the gap and larger than half its value [2], h essentially depends on the blade geometry [3][4][5], h increases with the blade inclination and slightly decreases with the blade velocity [5], shear-thinning effects increases h which remains smaller than the gap [3][4][6][7], elastic effects are in competition with viscous ones, decreasing h [3,4,8]. Some of these works present flow visualizations through streamlines [4][5][6] or qualitative direct observations [9]. It appears [9] that the flow shape and the volume of fluid at stake are strongly dependent on the fluid viscoelastic properties, leading to the formation of dead zones or even reverse flows.…”
Section: Introductionmentioning
confidence: 94%